The creatine content of Creatine Serum and the change in the plasma concentration with ingestion of a single dose - Harris, R. C.; Almada, A. L.; Harris, D. B.; Dunnett, M.; Hespel, P. (Journal of Sports Sciences, 2004)
Three samples of Creatine Serum ATP Advantage from Muscle Marketing USA, Inc. were assayed for creatine by two different techniques by four independent laboratories, and for creatinine by two different techniques by two laboratories. A further sample was assayed for phosphorylcreatine. Dry weight and total nitrogen were also analysed. Six male volunteers ingested in random order, over 3 weeks: (A) water; (B) 2.5 g creatine monohydrate (Cr.H2O) in solution; and (C) 5 ml Creatine Serum (reportedly containing an equivalent amount of Cr.H2O). Blood samples were collected before and up to 8 h after each treatment and plasma was analysed for creatine and creatinine. Eight-hour urine samples were analysed for creatine. Ingestion of 2.5 g creatine monohydrate in solution resulted in a significant increase in plasma creatine (from 59.1+/-11.8 micromol.l(-1) to 245.3+/-74.6 microM micromol.l(-1); mean+/-s) and urinary creatine excretion. No increase in plasma or urinary creatine or creatinine was found on ingestion of Creatine Serum or water. Analysis showed 5 ml of Creatine Serum to contain <10 mg Cr.H2O and approximately 90 mg creatinine. Phosphorylcreatine was not detectable and only a trace amount of phosphorous was present. Total nitrogen analysis ruled out significant amounts of other forms of creatine. We conclude that the trace amounts of creatine in the product would be too little to affect the muscle content even with multiple dosing.